Cassava as a feedstuff for ruminant feeding system in Belt and Road countries: innovations, benefits and challenges - Hossain, M.D.; Yan, Q.; Zhou, Z.; Zhang, X.; Wittayakun, S.; Napasirth, V.; Napasirth, P.; Lukuyu, Ben A. (Elsevier, 2025)
Cassava (Manihot esculenta), a versatile root crop, has garnered attention as a feedstuff for ruminant animals in Belt and Road Initiative (BRI) countries due to its widespread availability, adaptability, and high carbohydrate content. In numerous BRI countries, cassava was significant in supporting livestock industries from 2018 to 2022, especially in China, Senegal, Paraguay, Nigeria, and some African countries. This review delves into the diverse applications of cassava as an animal feed resource, with a focus on its nutrients, including carbohydrates, proteins, and minor components. It also discusses innovations, potential benefits, challenges, and possible mechanisms associated with utilizing cassava as an alternative feed source, particularly in ruminant diets. Effective techniques related to subduction of anti-nutrients and toxins, fiber degradation and protein enhancement, starch modification, and diet integration are described. Cassava products such as roots, leaves, and hay (whole crop), produced by these advanced techniques, have been demonstrated to improve growth performance, milk and meat quality, and body health when integrated into ruminant diets. Additionally, cassava by-products such as peels and foliage significantly contribution to animal feed, serving as an economical and efficient resource for farmers in BRI regions. Furthermore, multifaceted challenges related to variability in cassava quality, environmental concerns in production, and socioeconomic conflicts between feed, food and industrial uses are also pointed out. The information will provide practical ways for farmers to use cassava as ruminant feed, promote the application of more advanced technologies in cassava feeding, formulate national agricultural policies along the BRI regions, and ensure the global feed security.